Keterkaitan Spasial PDRB Sektor Pariwisata Kabupaten/Kota di Sumatera Utara - Yusmanda Endah Pangesti; Arifina Ratih (Departement of Mathematics Education, 2023)
This study aims to determine the spatial autocorelation of GRDP in the districts/cities tourism sector in North Sumatra. This study uses secondary data obtained from the Badan Pusat Statistik (BPS) of North Sumatra. The analytical method used is the Moran’s Index with secondary data in the form of the 2021 Gross Regional Domestic Product (GRDP). Based on the results of this analysis, each business field in the tourism sector has a Moran Index value of 0.2875 for trade, 0.4927 for transportation and warehousing, -0.103 for accommodation and food service activities, and 0.1043 for other service activities. Moran's Index value indicates a clustered spatial pattern in the trading, transportation and warehousing business fields, as well as other service activities, while the random spatial pattern is for the accommodation and food service activities. Based on the results of the Z test, it shows that there is a significant spatial autocorrelation in the GRDP of the tourism sector between districts/cities in North Sumatra.